Influence of addition of ginger on sensory quality, physicochemical properties and bioactivities of Malaysian multifloral honey - Yip, See Cheng (2022)
Honey and ginger are functional food with therapeutic values. Although their mixture is believed to exhibit various health benefits, scientific information on honey-ginger mixture is very limited. Therefore, this study aimed to investigate the influence of added Bentong ginger on sensory quality, physicochemical properties and bioactivities of multifloral honey produced by Apis cerena bee. In this study, the appearance, taste, aroma, texture and acceptability of ginger honey and base honey were assessed in sensory analysis. Physicochemical parameters evaluated were colour intensity, acidity, sugar content, moisture content, water activity and electrical conductivity. Also, antioxidant capacity of honey was measured using total phenolic content, hydroxyl radical scavenging activity, superoxide anion scavenging activity and iron chelating activity while antibacterial ability of honey was examined using agar well diffusion method. Results showed that ginger honey scored similarly to base honey for appearance, texture and most of the sensory attributes, except for the increased woody, chemical and spoiled but decreased sweetness, floral-fruity and warm attributes. However, the base honey was better accepted by the panelists. The colour intensity, pH, electrical conductivity and reducing sugar content of ginger honey (268.0-304.5 mAU; 4.48-4.88; 444.7-532.3 µS/cm; 59.64-61.92 %, respectively) were significantly higher than base honey (206.0 mAU; 4.53; 290.0 µS/cm; 57.12 %, respectively). Ginger honey also showed significant higher total phenolic content, superoxide anion scavenging activity and iron chelating activity (37.08-45.95 mg GAE/kg; 80.74-85.55 %; 13.32-21.28 %, respectively) than base honey (20.19 mg GAE/kg; 56.27 %; 1.64 %, respectively). All honey samples inhibited the growth of Escherichia coli and Staphylococcus aureus but no significant difference was found between their antibacterial capacities. Generally, addition of ginger into honey changed its physicochemical properties, taste and aroma but reduced its acceptability. The added ginger also enhanced the antioxidant ability but had no significant impact on the antibacterial capacity of honey.